Iron oxide-based electrode composite material suitable for lithium ion battery and preparation method of iron oxide-based electrode composite material

By using the preparation method of iron oxide-based electrode composite in lithium-ion batteries, the problem of capacity decay in repeated cycles is solved, and the effect of high cycle stability and extended battery life is achieved.

CN119725494APending Publication Date: 2025-03-28XINGXING ELECTRONIC NEW MATERIALS (WUXI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411991175.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The iron oxide electrode has severe capacity decay problems during repeated cycles of lithium-ion batteries, resulting in voltage hysteresis and low rate performance.

Method used

Using the preparation method of iron oxide-based electrode composite material, the iron oxide powder is mixed with carbon black powder ball mill, and added zinc chloride and deionized water stirred to form a zinc-iron carbon-based composite solution, followed by spray drying and gradient high-temperature calcination to form an iron oxide-based electrode composite material suitable for lithium-ion batteries.

Benefits of technology

The first reversible specific capacity and cycling stability of the iron oxide-based electrode composite material are improved, the material breakage caused by volume expansion is alleviated, the current transmission efficiency is enhanced, and the battery life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an iron oxide-based electrode composite material suitable for a lithium ion battery and a preparation method of the iron oxide-based electrode composite material, and belongs to the technical field of lithium ion electrode materials. The method comprises the following steps: ball-milling and mixing iron oxide powder and carbon black powder, adding zinc chloride and deionized water, and stirring to obtain a zinc-iron carbon-based composite solution; and carrying out continuous spray drying on the zinc-iron carbon-based composite solution, carrying out gradient high-temperature calcination, and cooling to room temperature to obtain the iron oxide-based electrode composite material suitable for the lithium ion battery. The prepared iron oxide-based electrode composite material suitable for the lithium ion battery has relatively good electrochemical performance, the first reversible specific capacity is relatively high, and the cycling stability after 20 times of cycling is greatly improved compared with that of a traditional electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion electrode materials, and in particular relates to an iron oxide-based electrode composite material suitable for lithium ion batteries and a preparation method thereof. Background Art

[0002] Iron oxide electrodes are mainly used as positive electrode materials in lithium-ion batteries and supercapacitors in electrochemical energy storage. Due to its fast reaction rate, high energy storage and release efficiency, and large capacity, iron oxide has been widely used in the field of electrochemical energy storage.

[0003] At present, iron oxide electrodes usually have serious capacity decay in repeated cycles, which may be related to the expansion / contraction of the volume of the electrode material after multiple cycles, causing fracture, resulting in severe voltage hysteresis and low rate performance. The above problems can be effectively solved by coating carbon-based materials or other methods of modification to form heterogeneous structures.

[0004] Based on this, developing an iron oxide-based electrode composite material suitable for lithium-ion batteries has become an urgent issue to be solved. Summary of the invention

[0005] The first object of the present invention is to provide an iron oxide-based electrode composite material suitable for lithium-ion batteries, which has a high first reversible specific capacity and good cycle stability.

[0006] The second object of the present invention is to provide a method for preparing an iron oxide-based electrode composite material, which is simple and easy to operate and suitable for large-scale mass production.

[0007] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing an iron oxide-based electrode composite material suitable for lithium ion batteries comprises the following steps: firstly, iron oxide powder and carbon black powder are ball-milled and mixed, and then zinc chloride and deionized water are added and stirred to obtain a zinc-iron carbon-based composite solution; the zinc-iron carbon-based composite solution is continuously spray-dried, and then gradient high-temperature calcined, and cooled to room temperature to obtain an iron oxide-based electrode composite material suitable for lithium ion batteries.

[0009] Furthermore, the mass ratio of the iron oxide powder to the carbon black powder is 2-3:2-0.5.

[0010] Furthermore, the mass ratio of the iron oxide powder to the carbon black powder is 3:2.

[0011] Furthermore, in the ball milling mixing, the ball-to-material ratio is 10:1, the ball milling speed is 300 rpm, and the ball milling time is 3 to 5 h.

[0012] Furthermore, the mass ratio of zinc chloride to deionized water is 1-3:50.

[0013] Furthermore, the temperature of continuous spray drying is 140-180°C, and the injection rate is controlled at 15%.

[0014] Furthermore, after the zinc-iron-carbon-based composite solution was continuously spray-dried, the average particle size of the obtained zinc-iron-carbon-based composite powder was 680 nm.

[0015] Furthermore, the gradient high temperature calcination is: calcination at 450°C for 60-85min, calcination at 480°C for 30-45min and calcination at 520°C for 15-30min.

[0016] Furthermore, the preparation method of any of the above-mentioned iron oxide-based electrode composite materials suitable for lithium-ion batteries comprises the following steps:

[0017] (1) Iron oxide powder and carbon black powder are mixed in a mass ratio of 2-3:2-0.5 and then ball milled, with a ball-to-material ratio of 10:1, a ball milling speed of 300 rpm, and a ball milling time of 3-5 h to obtain a mixed powder;

[0018] (2) adding zinc chloride and deionized water to the mixed powder obtained in step (1), wherein the mass ratio of the mixed powder, zinc chloride and deionized water is 3.5:1 to 3:50, and stirring continuously at 75° C. for 15 to 30 minutes to obtain a zinc-iron carbon-based composite solution;

[0019] (3) using a spray dryer to continuously spray dry the zinc-iron-carbon-based composite solution obtained in step (3), the drying temperature is controlled at 140-180° C., and the injection rate is controlled at 15%, to obtain a zinc-iron-carbon-based composite powder with an average particle size of 680 nm;

[0020] (4) The zinc-iron carbon-based composite powder obtained in step (4) is placed in a tubular furnace, and subjected to gradient high-temperature calcination under the protection of an argon or helium atmosphere, and then naturally cooled to room temperature to obtain an iron oxide-based electrode composite material suitable for lithium-ion batteries.

[0021] Furthermore, the iron oxide-based electrode composite material suitable for lithium-ion batteries is prepared by any of the above methods.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1) The iron oxide-based electrode composite materials suitable for lithium-ion batteries prepared by the present invention have good electrochemical properties, a high initial reversible specific capacity, and a greatly improved cycle stability after 20 cycles compared with traditional electrodes.

[0024] 2) The zinc-iron carbon-based composite material obtained by zinc doping modification in the present invention provides necessary space for the micro-expansion of the volume of the iron oxide-based electrode composite material during the charge and discharge process due to its own porosity and the constraint effect of the material skeleton, which can effectively alleviate the fracture of the material caused by sudden stress changes and improve the stability after multiple cycles.

[0025] 3) The iron oxide-based electrode composite material obtained by the stepwise calcination of the present invention can enhance the current transmission efficiency and reduce energy consumption, further provide a stable output current and extend the service life of the battery. DETAILED DESCRIPTION

[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0027] Unless otherwise specified, the raw materials used in the following examples are commercially available products.

[0028] The particle size of the iron oxide powder used in the following examples does not exceed 500 nm, and the particle size of the carbon black powder is 10-100 μm.

[0029] A method for preparing an iron oxide-based electrode composite material suitable for lithium-ion batteries, comprising the following steps:

[0030] (1) Iron oxide powder and carbon black powder are mixed in a mass ratio of 2-3:2-0.5 and then ball milled, with a ball-to-material ratio of 10:1, a ball milling speed of 300 rpm, and a ball milling time of 3-5 h to obtain a mixed powder;

[0031] (2) adding zinc chloride and deionized water to the mixed powder obtained in step (1), wherein the mass ratio of the mixed powder, zinc chloride and deionized water is 3.5:1 to 3:50, and stirring continuously at 75° C. for 15 to 30 minutes to obtain a zinc-iron carbon-based composite solution;

[0032] (3) using a spray dryer to continuously spray dry the zinc-iron-carbon-based composite solution obtained in step (3), the drying temperature is controlled at 140-180° C., and the injection rate is controlled at 15%, to obtain a zinc-iron-carbon-based composite powder with an average particle size of 680 nm;

[0033] (4) The zinc-iron carbon-based composite powder obtained in step (4) is placed in a tubular furnace, and subjected to gradient high-temperature calcination (calcination at 450°C for 60-85 min, calcination at 480°C for 30-45 min, and calcination at 520°C for 15-30 min) under the protection of an argon or helium atmosphere, and then naturally cooled to room temperature to obtain an iron oxide-based electrode composite material suitable for lithium-ion batteries.

[0034] Example 1

[0035] A method for preparing an iron oxide-based electrode composite material suitable for lithium-ion batteries comprises the following steps:

[0036] (1) Iron oxide powder and carbon black powder in a mass ratio of 3:2 were blended and then ball milled, with a ball-to-material ratio of 10:1, a ball milling speed of 300 rpm, and a ball milling time of 5 h to obtain a mixed powder;

[0037] (2) adding zinc chloride and deionized water to the mixed powder obtained in step (1), wherein the mass ratio of the mixed powder, zinc chloride and deionized water is 3.5:1:50, and stirring continuously at 75° C. for 30 minutes to obtain a zinc-iron carbon-based composite solution;

[0038] (3) using a spray dryer to continuously spray dry the zinc-iron-carbon-based composite solution obtained in step (3), the drying temperature is controlled at 180° C., and the injection rate is controlled at 15%, to obtain a zinc-iron-carbon-based composite powder with an average particle size of 680 nm;

[0039] (4) The zinc-iron carbon-based composite powder obtained in step (4) is placed in a tubular furnace, and subjected to gradient high-temperature calcination (calcination at 450°C for 85 min, calcination at 480°C for 30 min, and calcination at 520°C for 30 min) under the protection of an argon or helium atmosphere, and then naturally cooled to room temperature to obtain an iron oxide-based electrode composite material suitable for lithium-ion batteries.

[0040] Example 2

[0041] A method for preparing an iron oxide-based electrode composite material suitable for lithium-ion batteries comprises the following steps:

[0042] (1) Iron oxide powder and carbon black powder were mixed in a mass ratio of 1:1 and then ball-milled at a ball-to-material ratio of 10:1, a ball-milling speed of 300 rpm, and a ball-milling time of 5 h to obtain a mixed powder;

[0043] (2) adding zinc chloride and deionized water to the mixed powder obtained in step (1), wherein the mass ratio of the mixed powder, zinc chloride and deionized water is 3.5:2:50, and stirring continuously at 75° C. for 30 minutes to obtain a zinc-iron carbon-based composite solution;

[0044] (3) using a spray dryer to continuously spray dry the zinc-iron-carbon-based composite solution obtained in step (3), the drying temperature is controlled at 160° C., and the injection rate is controlled at 15%, to obtain a zinc-iron-carbon-based composite powder with an average particle size of 680 nm;

[0045] (4) The zinc-iron carbon-based composite powder obtained in step (4) is placed in a tubular furnace, and subjected to gradient high-temperature calcination (calcination at 450°C for 80 min, calcination at 480°C for 45 min, and calcination at 520°C for 15 min) under the protection of an argon or helium atmosphere, and then naturally cooled to room temperature to obtain an iron oxide-based electrode composite material suitable for lithium-ion batteries.

[0046] Example 3

[0047] A method for preparing an iron oxide-based electrode composite material suitable for lithium-ion batteries comprises the following steps:

[0048] (1) Iron oxide powder and carbon black powder were mixed in a mass ratio of 5:1 and then ball-milled at a ball-to-material ratio of 10:1, a ball-milling speed of 300 rpm, and a ball-milling time of 5 h to obtain a mixed powder;

[0049] (2) adding zinc chloride and deionized water to the mixed powder obtained in step (1), wherein the mass ratio of the mixed powder, zinc chloride and deionized water is 3.5:1:50, and stirring at 75° C. for 20 minutes to obtain a zinc-iron carbon-based composite solution;

[0050] (3) using a spray dryer to continuously spray dry the zinc-iron-carbon-based composite solution obtained in step (3), the drying temperature is controlled at 160° C., and the injection rate is controlled at 15%, to obtain a zinc-iron-carbon-based composite powder with an average particle size of 680 nm;

[0051] (4) The zinc-iron carbon-based composite powder obtained in step (4) is placed in a tubular furnace, and subjected to gradient high-temperature calcination (calcination at 450°C for 70 min, calcination at 480°C for 45 min, and calcination at 520°C for 15 min) under the protection of an argon or helium atmosphere, and then naturally cooled to room temperature to obtain an iron oxide-based electrode composite material suitable for lithium-ion batteries.

[0052] Example 4

[0053] A method for preparing an iron oxide-based electrode composite material suitable for lithium-ion batteries comprises the following steps:

[0054] (1) Iron oxide powder and carbon black powder were mixed in a mass ratio of 6:1 and then ball-milled at a ball-to-material ratio of 10:1, a ball-milling speed of 300 rpm, and a ball-milling time of 3 h to obtain a mixed powder;

[0055] (2) adding zinc chloride and deionized water to the mixed powder obtained in step (1), wherein the mass ratio of the mixed powder, zinc chloride and deionized water is 3.5:3:50, and stirring continuously at 75° C. for 30 minutes to obtain a zinc-iron carbon-based composite solution;

[0056] (3) using a spray dryer to continuously spray dry the zinc-iron-carbon-based composite solution obtained in step (3), the drying temperature is controlled at 140° C., and the injection rate is controlled at 15%, to obtain a zinc-iron-carbon-based composite powder with an average particle size of 680 nm;

[0057] (4) The zinc-iron carbon-based composite powder obtained in step (4) is placed in a tubular furnace, and subjected to gradient high-temperature calcination (calcination at 450°C for 60 min, calcination at 480°C for 30 min, and calcination at 520°C for 25 min) under the protection of an argon or helium atmosphere, and then naturally cooled to room temperature to obtain an iron oxide-based electrode composite material suitable for lithium-ion batteries.

[0058] Example 5

[0059] A method for preparing an iron oxide-based electrode composite material suitable for lithium-ion batteries, comprising the following steps:

[0060] (1) Iron oxide powder and carbon black powder in a mass ratio of 4:1 were blended and then ball-milled at a ball-to-material ratio of 10:1, a ball milling speed of 300 rpm, and a ball milling time of 3 to 5 h to obtain a mixed powder;

[0061] (2) adding zinc chloride and deionized water to the mixed powder obtained in step (1), wherein the mass ratio of the mixed powder, zinc chloride and deionized water is 3.5:1:50, and stirring continuously at 75° C. for 30 minutes to obtain a zinc-iron carbon-based composite solution;

[0062] (3) using a spray dryer to continuously spray dry the zinc-iron-carbon-based composite solution obtained in step (3), the drying temperature is controlled at 180° C., and the injection rate is controlled at 15%, to obtain a zinc-iron-carbon-based composite powder with an average particle size of 680 nm;

[0063] (4) The zinc-iron carbon-based composite powder obtained in step (4) is placed in a tubular furnace, and subjected to gradient high-temperature calcination (calcination at 450°C for 85 min, calcination at 480°C for 35 min, and calcination at 520°C for 15 min) under the protection of an argon or helium atmosphere, and then naturally cooled to room temperature to obtain an iron oxide-based electrode composite material suitable for lithium-ion batteries.

[0064] Comparative Example 1

[0065] A method for preparing an iron oxide-based electrode composite material, comprising the following steps:

[0066] (1) Iron oxide powder and carbon black powder in a mass ratio of 1:2 were blended and then ball milled, with a ball-to-material ratio of 10:1, a ball milling speed of 300 rpm, and a ball milling time of 3 to 5 h to obtain a mixed powder;

[0067] (2) adding deionized water to the mixed powder obtained in step (1), wherein the mass ratio of the mixed powder to the deionized water is 0.7:10, and stirring continuously at 75° C. for 30 minutes to obtain a carbon-containing iron-based solution;

[0068] (3) using a spray dryer to continuously spray dry the carbon-containing iron-based solution obtained in step (3), wherein the drying temperature is controlled at 220° C. and the injection rate is controlled at 15%, to obtain a carbon-containing iron-based mixed powder;

[0069] (4) The carbon-containing iron-based mixed powder obtained in step (4) is placed in a tubular furnace, and subjected to gradient high-temperature calcination (calcination at 450°C for 85 min, calcination at 480°C for 30 min, and calcination at 520°C for 30 min) under the protection of an argon or helium atmosphere, and then naturally cooled to room temperature to obtain an iron oxide-based electrode composite material.

[0070] Comparative Example 2

[0071] (1) blending iron oxide powder and carbon black powder in a mass ratio of 3:2 to obtain a mixed powder;

[0072] (2) adding zinc chloride and deionized water to the mixed powder obtained in step (1), wherein the mass ratio of the mixed powder, zinc chloride and deionized water is 3.5:1:50, and stirring continuously at 75° C. for 30 minutes to obtain a zinc-iron carbon-based composite solution;

[0073] (3) drying the zinc-iron-carbon-based composite solution obtained in step (3), wherein the drying temperature is controlled to be 180° C., to obtain a zinc-iron-carbon-based composite powder;

[0074] (4) The zinc-iron carbon-based composite powder obtained in step (4) is placed in a tubular furnace, and subjected to gradient high-temperature calcination (calcination at 450°C for 85 min, calcination at 480°C for 30 min, and calcination at 520°C for 30 min) under the protection of an argon or helium atmosphere, and then naturally cooled to room temperature to obtain an iron oxide-based electrode composite material.

[0075] Comparative Example 3

[0076] (1) Iron oxide powder and carbon black powder in a mass ratio of 3:2 were blended and then ball milled, with a ball-to-material ratio of 10:1, a ball milling speed of 300 rpm, and a ball milling time of 5 h to obtain a mixed powder;

[0077] (2) adding zinc chloride and deionized water to the mixed powder obtained in step (1), wherein the mass ratio of the mixed powder, zinc chloride and deionized water is 3.5:1:50, and stirring continuously at 75° C. for 30 minutes to obtain a zinc-iron carbon-based composite solution;

[0078] (3) using a spray dryer to continuously spray dry the zinc-iron-carbon-based composite solution obtained in step (3), the drying temperature is controlled at 180° C., and the injection rate is controlled at 15%, to obtain a zinc-iron-carbon-based composite powder with an average particle size of 680 nm;

[0079] (4) The zinc-iron carbon-based composite powder obtained in step (4) is placed in a tubular furnace, and calcined at high temperature (calcined at 520° C. for 160 min) under the protection of an argon or helium atmosphere, and then naturally cooled to room temperature to obtain an iron oxide-based electrode composite material.

[0080] The iron oxide-based electrode composite materials prepared in the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 3 were mixed with acetylene black and CMC to form slurries (wherein the slurry contained 80wt.% of the iron oxide-based electrode composite material, 10wt.% of acetylene black and 10wt.% of CMC), and evenly coated on copper sheets or copper foils, and then vacuum dried and punched to form electrode sheets. A test cell was formed with metallic lithium as the negative electrode, a copper sheet or copper foil coated with the iron oxide-based electrode composite material as the positive electrode, 1mol / L LiPF6 / EC+DEC+DMC (volume ratio of 1:1:1) as the electrolyte, and Celgard 2400 as the diaphragm. The battery was charged and discharged, and the test results are shown in Table 1 below. Among them, the voltage range of charge and discharge was controlled at 0.02~3.0V, and the current density was 0.1A / g.

[0081] Table 1 Comparison of the charge and discharge performance of lithium-ion batteries prepared from the iron oxide-based electrode composite materials in Examples 1 to 5 and Comparative Examples 1 to 3

[0082]

[0083] It can be seen from Table 1 that the iron oxide-based electrode composite materials suitable for lithium-ion batteries prepared in Examples 1 to 5 of the present invention all have good electrochemical properties, the first reversible specific capacity is significantly higher than that of Comparative Examples 1 to 3, and the cycle stability after 20 cycles is also greatly improved.

[0084] By comparing Example 1 of the present invention with Comparative Example 1, it can be obtained that the zinc-iron carbon-based composite material obtained by adding zinc provides necessary space for the micro-expansion of the volume of the iron oxide-based electrode composite material during the charge and discharge process due to its own porosity and the constraint effect of the material skeleton, which can effectively alleviate the breakage of the material caused by sudden stress changes and improve the stability after multiple cycles.

[0085] By comparing Example 1 with Comparative Example 2, it can be seen that ball milling of iron oxide powder and carbon black powder can increase the surface area of ​​iron oxide and carbon base, further improving the electrochemical activity of the material; and spray drying can effectively inhibit the self-heating reaction of the battery, provide higher energy density, improve the endurance of lithium-ion batteries and extend the service life of the battery, and maintain the stability of the battery after multiple discharge and charge tests.

[0086] Compared with Examples 1 to 5 and Comparative Example 3, the iron oxide-based electrode composite material obtained by the staged calcination (i.e., calcination at 450° C. for 60 to 85 min, calcination at 480° C. for 30 to 45 min, and calcination at 520° C. for 15 to 30 min) in the present invention can enhance the current transmission efficiency and reduce energy consumption, further provide a stable output current, and extend the service life of the battery.

[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an iron oxide-based electrode composite material suitable for lithium-ion batteries, characterized in that: The iron oxide powder and the carbon black powder are first ball-milled and mixed, and then zinc chloride and deionized water are added and stirred to obtain a zinc-iron carbon-based composite solution; the zinc-iron carbon-based composite solution is continuously spray-dried, and then gradient high-temperature calcined, and after cooling to room temperature, an iron oxide-based electrode composite material suitable for lithium-ion batteries is obtained.

2. The method for preparing the iron oxide-based electrode composite material suitable for lithium-ion batteries according to claim 1, characterized in that: The mass ratio of the iron oxide powder to the carbon black powder is 2-3:2-0.

5.

3. The method for preparing the iron oxide-based electrode composite material suitable for lithium-ion batteries according to claim 2, characterized in that: The mass ratio of the iron oxide powder to the carbon black powder is 3:

2.

4. The method for preparing the iron oxide-based electrode composite material suitable for lithium-ion batteries according to claim 1, characterized in that: In the ball milling mixing, the ball-to-material ratio is 10:1, the ball milling speed is 300 rpm, and the ball milling time is 3 to 5 hours.

5. The method for preparing the iron oxide-based electrode composite material suitable for lithium-ion batteries according to claim 1, characterized in that: The mass ratio of zinc chloride to deionized water is 1~3:

50.

6. The method for preparing the iron oxide-based electrode composite material suitable for lithium-ion batteries according to claim 1, characterized in that: The temperature of continuous spray drying was 140~180℃, and the injection rate was controlled at 15%.

7. The method for preparing the iron oxide-based electrode composite material suitable for lithium-ion batteries according to claim 1, characterized in that: After the zinc-iron-carbon-based composite solution is continuously spray-dried, the average particle size of the obtained zinc-iron-carbon-based composite powder is 680 nm.

8. The method for preparing the iron oxide-based electrode composite material suitable for lithium-ion batteries according to claim 1, characterized in that: The gradient high temperature calcination is: calcination at 450° C. for 60 to 85 min, calcination at 480° C. for 30 to 45 min, and calcination at 520° C. for 15 to 30 min.

9. The method for preparing the iron oxide-based electrode composite material suitable for lithium ion batteries according to any one of claims 1 to 8, characterized in that: Here are the steps: (1) Iron oxide powder and carbon black powder are mixed in a mass ratio of 2-3:2-0.5 and then ball milled, with a ball-to-material ratio of 10:1, a ball milling speed of 300 rpm, and a ball milling time of 3-5 h to obtain a mixed powder; (2) adding zinc chloride and deionized water to the mixed powder obtained in step (1), wherein the mass ratio of the mixed powder, zinc chloride and deionized water is 3.5:1 to 3:50, and stirring continuously at 75° C. for 15 to 30 minutes to obtain a zinc-iron carbon-based composite solution; (3) using a spray dryer to continuously spray dry the zinc-iron-carbon-based composite solution obtained in step (3), the drying temperature is controlled at 140-180° C., and the injection rate is controlled at 15%, to obtain a zinc-iron-carbon-based composite powder with an average particle size of 680 nm; (4) The zinc-iron carbon-based composite powder obtained in step (4) is placed in a tubular furnace, and subjected to gradient high-temperature calcination under the protection of an argon or helium atmosphere, and then naturally cooled to room temperature to obtain an iron oxide-based electrode composite material suitable for lithium-ion batteries.

10. An iron oxide-based electrode composite material suitable for lithium-ion batteries prepared according to the method of any one of claims 1 to 9.